Pengaruh Tourism Destination Image Terhadap Revisit Intention yang Dimediasi oleh Tourism Satisfaction Pantai Cemara Cianjur - Surya Pratama Nugraha; Hariyadi Triwahyu Putra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the influence of cognitive destination image and affective destination image on revisit intention, with tourism satisfaction as a mediating variable for tourists visiting Pantai Cemara, Cidaun, Cianjur. The background of this research is based on the phenomenon of increasing tourist visits to West Java Province, which is not accompanied by a rise in visits to Pantai Cemara. This study employs a descriptive and verificative quantitative approach. The sampling technique used is non-probability sampling with a purposive sampling method. Data were collected from 120 respondents who had previously visited Pantai Cemara. Data analysis was carried out using multiple regression analysis and the Sobel test to examine the mediating role. The findings indicate that both cognitive destination image and affective destination image have a positive and significant effect on tourism satisfaction. Moreover, both destination image variables also positively influence revisit intention. However, tourism satisfaction was found to significantly mediate the relationship between cognitive destination image and revisit intention, while no significant mediation effect was observed in the relationship between affective destination image and revisit intention. These results suggest that enhancing both cognitive and affective perceptions of a destination can improve tourist satisfaction and revisit intention, with cognitive destination image playing a stronger role in mediating satisfaction and revisit intention. The implications of this research are expected to provide practical insights for tourism managers at Pantai Cemara in designing more effective destination management and promotional strategies to increase tourist loyalty.